Reduced serum calcium is a risk factor for febrile seizures - B., Ushakiran C.; R., Suresh (International Journal of Contemporary Pediatrics, 2017)
Background: Febrile seizure (FS) is the most common cause of convulsions in children. The objective of present work was to study the association between serum electrolytes and febrile seizures. Methods: Children in the age group of 6 month to 6 years with febrile seizures satisfying inclusion criteria and equal number of age and sex matched controls were subjected to estimation serum electrolytes and compared using appropriate statistical methods. Results: Serum Calcium levels in children with febrile seizures were reduced and this observation was statistically significant. Conclusions: Definite association was found between serum calcium levels and the occurrence of febrile seizures. Although serum calcium levels were not in the hypocalcemic range, they were decreased enough to cause a statistical significance in precipitating febrile seizures.